2016
DOI: 10.3749/canmin.1600021
|View full text |Cite
|
Sign up to set email alerts
|

Monazite-(Ce) and Xenotime-(Y) From An Lct, NYF Tertiary Pegmatite Field: Evidence From A Regional Study In the Central Alps (Italy and Switzerland)

Abstract: Monazite-(Ce) and xenotime-(Y) from tertiary pegmatites of the central Alps (Italy and Switzerland) were studied by EMPA and SCXRD analytical methods. The REE-phosphate minerals analyzed are from LCT and NYF pegmatite dikes of the Central Alps, which includes three main areas: Vigezzo (LCT and NYF from the Vigezzo valley), Bodengo (NYF from the Leggia valley and LCT from the Cama valley), and Codera (LCT from Codera and Chiavenna valleys and Alpe Rossaccio). SEM-BSE images of monazite-(Ce) show primary growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The dike is asymmetric, with zones characterized by different mineral associations. Triplite masses, up to 5 mm in diameter, occur in a zone strongly enriched in dark green to brownish yellow elbaite and colorless to pale pink beryl (Guastoni 2012). In thin section, triplite occurs as deeply fractured rounded masses; fractures are sharp and filled with Mn oxides.…”
Section: Background Informationmentioning
confidence: 99%
“…The dike is asymmetric, with zones characterized by different mineral associations. Triplite masses, up to 5 mm in diameter, occur in a zone strongly enriched in dark green to brownish yellow elbaite and colorless to pale pink beryl (Guastoni 2012). In thin section, triplite occurs as deeply fractured rounded masses; fractures are sharp and filled with Mn oxides.…”
Section: Background Informationmentioning
confidence: 99%
“…However, the presence of REE at the Asite, according to Speer (1982), may enlarge the stability field of huttonite to lower temperatures. Harlov et al (2007) found out that the crystallization of metastable huttonite at the expenses of monazite-(Ce) crystals can take place at 400° C (and 500 MPa), in the thorite field, as also reported by Guastoni et al (2016) for pegmatitic monazites of the Central Alps. In this light, given the difficulty to tell apart thorite and huttonite by means of EPMA analyses Harlov and Föster, 2002) and the lack of information on the (P,T) conditions of the hydrothermal fluids of Mt.…”
Section: Chemical Composition Of the Chernovite-(y)-xenotime-(y) Seriesmentioning
confidence: 69%
“…5d) shows very scattered results, exhibiting relatively consistent concentrations of Y, while concentrations of HREE vary extensively. Lack of grouping and scattered results point towards the origin of xenotime from variable geological backgrounds (Guastoni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%